2011
DOI: 10.1007/s10956-011-9326-z
|View full text |Cite
|
Sign up to set email alerts
|

Filling in the Distance Between Us: Group Metacognition During Problem Solving in a Secondary Education Course

Abstract: While a body of research exists on individual metacognition, research on reflective communities is just beginning. This study generated a framework for conceptualizing metacognition in groups by describing likely components of group metacognition. I focused on a group of five preservice science teachers engaged in problembased learning (PBL). The purpose of the PBL course was to help students gain useful concepts from the learning sciences to apply to teaching. I investigated forms of metacognition and the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 49 publications
(39 reference statements)
0
14
0
13
Order By: Relevance
“…Sendo a PBL uma atividade realizada em grupo, acredita-se que os componentes da metacognição, descritos por Siegel (2012), estejam presentes no desenvolvimento de grupos de PBL. Na resolução dos problemas, as estratégias metacognitivas são socializadas quando explicitadas pelos integrantes, podendo ser ampliadas e aperfeiçoadas com a contribuição de cada pessoa na interação grupal.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Sendo a PBL uma atividade realizada em grupo, acredita-se que os componentes da metacognição, descritos por Siegel (2012), estejam presentes no desenvolvimento de grupos de PBL. Na resolução dos problemas, as estratégias metacognitivas são socializadas quando explicitadas pelos integrantes, podendo ser ampliadas e aperfeiçoadas com a contribuição de cada pessoa na interação grupal.…”
Section: Resultsunclassified
“…PBL ou aprendizagem baseada em problema é um método de instrução específico que envolve a resolução colaborativa de problemas por meio de intensa discussão e pesquisa (SIEGEL, 2012). Foi desenvolvido pela primeira vez em programas de escola médica (BARROWS, 1988;HUNG;JONASSEN;LIU, 2008) e adaptado em outras áreas profissionais (como Direito, negócios), em universidades, escolas secundárias e primárias.…”
Section: Pbl -Problem-based Learning: Aprendizagem Baseada Em Problemaunclassified
See 1 more Smart Citation
“…Research has shown that collaborative learning has the potential to develop metacognition (e.g., Larkin, ; Nielsen et al, ; Siegel, ). According to Frith (), collaboration and metacognition are mutually related.…”
Section: Supporting Students' Metacognition Through Peer Collaborationmentioning
confidence: 99%
“…As a result when students are faced with problems, students have difficulty to solve them. So that's way, teachers are required to develop new nuances in teaching and learning process to improve the quality of learning one by empowering metacognition skills (Siegel 2012). …”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%